2014
DOI: 10.1016/j.jad.2014.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar disorder with comorbid binge eating history: A genome-wide association study implicates APOB

Abstract: Background Bipolar disorder (BD) is a highly heritable disease. While genome-wide association (GWA) studies have identified several genetic risk factors for BD, few of these studies have investigated the genetic etiology of specific disease subtypes. In particular, BD is positively associated with eating dysregulation traits such as binge eating behavior (BE), yet the genetic risk factors underlying BD with comorbid BE have not been investigated. Methods Utilizing data from the Genetic Association Informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 50 publications
(59 reference statements)
2
31
1
3
Order By: Relevance
“…In the brain, mTOR is important for neuronal development, synaptic plasticity, and axonal regeneration and limits astrocytic scar formation [46]. PRR5 was recently associated to bipolar disorder [47]. The PRR12 mRNA was also identified as a target of FMRP [27].…”
Section: Discussionmentioning
confidence: 99%
“…In the brain, mTOR is important for neuronal development, synaptic plasticity, and axonal regeneration and limits astrocytic scar formation [46]. PRR5 was recently associated to bipolar disorder [47]. The PRR12 mRNA was also identified as a target of FMRP [27].…”
Section: Discussionmentioning
confidence: 99%
“…For mtSNPs showing the strongest associations based on the joint tests, genome-wide analyses were repeated using imputed SNP data to generate Manhattan plots and locus zoom plots. Genome-wide imputation for the GAIN BD data was conducted using the 1,000 Genome Project cosmopolitan reference panel, and the detailed procedures have been previously described [44]. …”
Section: Methodsmentioning
confidence: 99%
“…Unsurprisingly, several modestly powered GWAS studies for ED-related traits reported negative findings after correcting for multiple testing [79,80]. A recent negative two-stage GWAS meta-analysis for AN in 5,551 cases and 21,080 controls concluded that the accrual of large genotyped AN case-control samples should be an immediate priority for the field to identify AN-predisposing genes [81].…”
Section: Genome-wide Association Studiesmentioning
confidence: 99%
“…The only genomewide CNV study of EDs reported a 1.4-Mb deletion on 13q12 in 2 AN cases [80]. A genome-wide search for copy-number variants associated with BMI, found a 600-Kb deletion on chromosome 16p11.2 associated with a highly penetrant form of obesity accompanied by hyperphagia and increased ad libitum food intake [92,93].…”
Section: Copy Number Variantsmentioning
confidence: 99%